PEMANFAATAN SMARTPHONE SEMAKSIMAL MUNGKIN: DIGITALISASI PRODUK KEBAHASAAN KE DALAM APLIKASI SEBAGAI SOLUSI MITIGASI PERGESERAN BAHASA JAWA - Aribowo, Eric Kunto (MAGISTRA, 2015)
We humans live in a world of just 194 countries, give or take, but speak between 6,000 and7,000 languages. And now the globalization of media and technology are hastening the trend toward linguistichomogeneity. According to some linguists, 90% of local languages will disappear by the end of the 21st century.Despite the thousands of languages that exist today, 80% of the planet communicates in just 83 languages. Itmeans that there is no doubt that technology has had a âsignificant impactâ on language in the last 10 years.Progress and development of Information and Communications Technology (ICT) should have a positive influenceon the existence of local languages. This paper provides an alternative solution in the use of technology,particularly smartphone, in order to overcome the language shift and facing the language extinction.Keywords: languangemaintenance, Javanese shift, apps smartphone